Direct identification of sickle cell anemia by blot hybridization. - Geever, R F (1981)
Several reports have been published on the use of polymorphisms found in the human hemoglobin genes as a means for prenatal diagnosis of sickle cell anemia. The disadvantages of this approach reside in its limited application and the need for family analysis. Here we report that, by use of restriction endonuclease Dde I and diazobenzyloxymethyl-paper transfer procedures, a direct analysis can be made. Individuals with normal hemoglobin (AA) show two bands (175 and 201 base pairs) complementary to a 5'-specific beta-globin gene probe. Sickle cell trait individuals (AS) exhibit an additional band (376 base pairs). Individuals with sickle cell anemia (SS) show the band at 376 base pairs with a concomitant loss of the 175-base pair band. We interpret these changes in banding pattern to be the result of the elimination of a restriction site for Dde I in the altered codon associated with the sickle cell allele. Because an analysis can be performed on as little as 20 micrograms of cellular DNA, the application to prenatal diagnosis of sickle cell anemia should be possible.